The convergence of environmental innovation, stakeholder pressure, open innovation in logistics firms: pathway to renewable energy in the presence of managerial cognition & competitive advantage - Sadiq, Muhammad; Chien, Fengsheng; Staniewski, Marcin Waldemar; Tufail, Bushra (Technological and Economic Development of Economy, 2025)
The logistics industry has recently been pressured to adopt sustainable practices due to increasing environmental concerns and regulatory mandates. This study investigates the nexus between ecological innovation, stakeholder pressure, open innovation, and renewable energy adoption in logistics firms, emphasizing the moderating role of managers’ cognition of sustainable opportunities and competitive advantage. In this regard, stakeholder pressure compels organizations to adopt renewable solutions. On the other hand, open innovation and eco-innovation are pivotal in taming firms’ internal limitations and advancing the adoption of renewable technologies. Thereby, analyzing empirical data from China’s logistics firm, the present study demonstrates how open innovation, eco-innovation, and stakeholder pressure affect renewable energy adoption and the firm’s competitive advantage. In addition, the study explicitly outlines the critical role of managers’ cognition of sustainable opportunities and competitive advantage as a moderator. Through SEM, the study reveals a positive and significant relationship between open-innovation, eco-innovation, and stakeholders’ pressures regarding renewable energy adoption. The moderation of managers’ cognition in the case of eco-innovation and open innovation proved significant, whereas, in the case of stakeholder pressure, it is insignificant. Competitive advantage, another moderator, failed to moderate the proposed relationship. Findings explain that managers can realize strategic significance in terms of sustainability. They may shift toward green strategies aligned with market apprehensions and environmental regulations. This cognitive factor enhances the usefulness of open and eco-innovation during renewable adoption. Overall, the study’s findings underscore the significance of managerial insights in leveraging these factors to accelerate the industry toward a sustainable future.